ISU-ISU DALAM BIMBINGAN DAN KONSELING - Siahaan, Dina Nadira Amelia; Zunidar, Zunidar (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The development of science, technology, family and social life has brought changes and problems in human life that always require adjustments in living the wheel of life. In responding to this condition, all matters relating to human needs, interactions and lifestyles must be adapted to the conditions prevailing at that time. Phenomena in various issues that arise in BK include individual, social and career issues that are continuously developing in reality. This has also brought changes to the world of guidance and counseling. Guidance and counseling must be ready and willing to meet current human needs in the form of efforts to help solve problems that often occur. Therefore, the existence of guidance and counseling must continue to be updated on the development of science and all individuals at that time.